Scale insect genus-group names and their families (Hemiptera: Sternorrhyncha: Coccoidea) - Williams, Douglas J.; Denno, Barbara D. (Zootaxa, 2014)
Genus names of the scale insects (Hemiptera: Coccoidea) are listed with their current families. The list includes all generic names that are currently valid with synonyms, unjustified emendations, homonyms, nomia nuda and misspellings. The list has been compiled from many sources as discussed in the introduction. This is the first list to be prepared in recent years of all generic names and it is in alphabetical order.